2017
DOI: 10.1007/s00011-017-1040-8
|View full text |Cite
|
Sign up to set email alerts
|

Probucol attenuates overt pain-like behavior and carrageenan-induced inflammatory hyperalgesia and leukocyte recruitment by inhibiting NF-кB activation and cytokine production without antioxidant effects

Abstract: Probucol presents analgesic and anti-inflammatory activities by employing mechanisms other than its antioxidant properties. These mechanisms involve targeting of pro-inflammatory cytokines and NF-кB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Our results, along with those demonstrating that probucol can reduce lipopolysaccharide- carrageenan-, and CFA-induced mechanical allodynia and thermal hyperalgesia ( Zucoloto et al, 2017a , Zucoloto et al, 2017b , Zucoloto et al, 2019 ), as well as the neuropathy produced by chronic constriction nerve injury ( Derangula et al, 2022 ), suggest probucol (or its congener, succinobucol (4-[2,6-di- tert -butyl-4-[2-(3,5-di- tert -butyl-4-hydroxyphenyl)sulfanylpropan-2-ylsulfanyl]phenoxy]-4-oxobutanoic acid; probucol with a succinate adduct in the 4-position of the second 2,6-DTBP group) may be an effective, non-opioid, oral antihyperalgesic. That probucol can be chronically and safely orally administered to humans ( Yamashita and Matsuzawa, 2009 ) and succinobucol has completed Phase III clinical trials ( Tardif et al, 2003 , Tardif et al, 2008b , Tardif et al, 2008a ) suggests testing either drug could proceed expeditiously.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results, along with those demonstrating that probucol can reduce lipopolysaccharide- carrageenan-, and CFA-induced mechanical allodynia and thermal hyperalgesia ( Zucoloto et al, 2017a , Zucoloto et al, 2017b , Zucoloto et al, 2019 ), as well as the neuropathy produced by chronic constriction nerve injury ( Derangula et al, 2022 ), suggest probucol (or its congener, succinobucol (4-[2,6-di- tert -butyl-4-[2-(3,5-di- tert -butyl-4-hydroxyphenyl)sulfanylpropan-2-ylsulfanyl]phenoxy]-4-oxobutanoic acid; probucol with a succinate adduct in the 4-position of the second 2,6-DTBP group) may be an effective, non-opioid, oral antihyperalgesic. That probucol can be chronically and safely orally administered to humans ( Yamashita and Matsuzawa, 2009 ) and succinobucol has completed Phase III clinical trials ( Tardif et al, 2003 , Tardif et al, 2008b , Tardif et al, 2008a ) suggests testing either drug could proceed expeditiously.…”
Section: Discussionsupporting
confidence: 77%
“…In adult male Swiss mice, probucol (3 mg/kg, oral administration) reduces lipopolysaccharide- and carrageenan-induced mechanical allodynia and thermal hyperalgesia ( Zucoloto et al, 2017a , Zucoloto et al, 2017b ). These effects were accompanied by reduced leukocyte influx and cytokine production in both paw skin and peritoneum exudate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of inflammation and the generation of pain have a strong connection. Since exposure to radiation caused a significant increase in the volume of the paw, it was therefore expected that the nociceptive threshold would decrease significantly after the exertion of mechanical hyperalgesia on the irradiated paw of rats (Randall & Selitto, 1957 ; Oka et al., 2007 ; Zucoloto et al., 2017 ). Controversially, the present study showed no significant difference between the nociceptive threshold recorded in the inflamed irradiated rats and that observed in the inflamed group.…”
Section: Discussionmentioning
confidence: 99%